THE STATISTICAL ASSESSMENT OF THE TRAFFIC SITUATION BASED ON SAMPLE DATA OF TRAFFIC ACCIDENTS IN THE URBAN AGGLOMERATION - Kushchenko, Liliya; Кущенко, Сергей; Новиков, Александр; Королева, Лилия (Journal of Applied Engineering Science, 2023)
The article analyzes the accident rate on the roads at the entrance sections of the Belgorod agglomeration road network with the help of a documentary study of traffic accident records for the statistical assessment of the road traffic situation. It has been established that collisions and hitting a pedestrian are particular types of traffic accidents. The results of the analysis showed that Tuesday and Sunday are among the peak days of the week in terms of the probability of traffic accidents. Calculations based on mathematical statistics and probability theory have shown that there is a correlation between the number of accidents and the proposed characteristic hours of the day. To improve road safety, an information model was developed, an information model for reducing traffic accidents in places of concentration of traffic accidents.
Keywords: traffic accident, types of traffic accidents, vehicle, mathematical statistics, information model